MANAGEMENT OF COMMUNICATION INNOVATIONS FOR THE DEVELOPMENT OF LIONS CLUBS INTERNATIONAL ORGANIZATION IN REGION 310, THAILAND - Chodchanaprasit, Kanyaluck (Journal of MCU Nakhondhat, 2025)
The study on the management of communication innovation for the development of Lions Clubs International District 310, Thailand has the following objectives: 1) To study the use and management of communication innovation within the organization 2) To study the supporting factors and obstacles affecting the management of communication innovation 3) To study and determine the guidelines for communication innovation to develop 4) To analyze the results of innovation management in communication. Mixed Method Research by using qualitative research using documentary research methods along with in-depth interviews. The primary informants were senior executives, middle executives, communications operations, academic experts, and members of Lions Clubs International, District 310, Thailand. The research methodology was document research, coupled with in-depth interviews with key informants, namely, senior executives, middle executives, communications practitioners, academics, and members of Lions Clubs International, District 310, Thailand. The research results found that: The most used and managed communication innovation is new media. The most common communication channel is Line. Frequency/frequency is 1 - 4 times/week. Duration: More than 15 minutes - 30 minutes. Issues or objectives are to coordinate activities and create management standards. Supporting factors and obstacles affecting communication innovation management, the first is freedom of thought. The factors affecting communication within the organization, the first is communication channels, followed by club services and recipients. Communication innovation guidelines for organizational development There are guidelines for developing innovations in line with global changes. Results of managing innovation in current and future communication There is a form of managing communication innovation within the organization through the form of social service activities. There is support from foundations, donations from members to support local community development.